"Cystic"‐appearing soft tissue masses: What is the role of anatomic, functional, and metabolic MR imaging techniques in their characterization?. Issue 3 (22nd October 2013) - Thawait, Gaurav K.; Subhawong, Ty K.; Tatizawa Shiga, Ney Yoichi; Fayad, Laura M.
Abstract : Although conventional MR imaging with contrast‐enhanced T1‐weighted sequences is of paramount importance for evaluating soft tissue masses, noncontrast MR sequences have emerged that facilitate their characterization. In this article, the utility and pitfalls of conventional MR imaging with T1‐weighted, fluid‐sensitive, and contrast‐enhanced sequences will be discussed, along with that of functional (diffusion weighted imaging) and metabolic (proton MR spectroscopy) non–contrast‐enhanced techniques for the purpose of soft tissue mass characterization. In particular, we discuss the application of these techniques to differentiating neoplastic or inflammatory masses that have high fluid content from benign cysts, as this distinction is a common pitfall of conventional sequences.J. Magn. Reson. Imaging 2014;39:504–511 . ©2013 Wiley Periodicals, Inc .